Contextual Feedback to Superficial Layers of V1 - Muckli, Lars; De Martino, Federico; Vizioli, Luca; Petro, Lucy S.; Smith, Fraser W.; Ugurbil, Kamil; Goebel, Rainer; Yacoub, Essa (Current biology, 2015)
Neuronal cortical circuitry comprises feedforward, lateral, and feedback projections, each of which terminates in distinct cortical layers [1–3]. In sensory systems, feedforward processing transmits signals from the external world into the cortex, whereas feedback pathways signal the brain’s inference of the world [4–11]. However, the integration of feedforward, lateral, and feedback inputs within each cortical area impedes the investigation of feedback, and to date, no technique has isolated the feedback of visual scene information in distinct layers of healthy human cortex. We masked feedforward input to a region of V1 cortex and studied the remaining internal processing. Using high-resolution functional brain imaging (0.8 mm3) and multivoxel pattern information techniques, we demonstrate that during normal visual stimulation scene information peaks in mid-layers. Conversely, we found that contextual feedback information peaks in outer, superficial layers. Further, we found that shifting the position of the visual scene surrounding the mask parametrically modulates feedback in superficial layers of V1. Our results reveal the layered cortical organization of external versus internal visual processing streams during perception in healthy human subjects. We provide empirical support for theoretical feedback models such as predictive coding [10, 12] and coherent infomax [13] and reveal the potential of high-resolution fMRI to access internal processing in sub-millimeter human cortex. [Display omitted] •High-resolution MRI shows functional information patterns in non-stimulated V1•Non-stimulated V1 receives cortical feedback information to superficial layers•Feedback to non-stimulated V1 superficial layers is predictive of visual context Muckli et al. have discovered that the superficial layers of visual cortex V1 receive information when not directly stimulated. This information contains contextual feedback from higher visual areas. The data provide empirical evidence for layer-specific cortical feedback relevant for the neurobiology of predictive coding.